2004
DOI: 10.1007/s00122-004-1758-x
|View full text |Cite
|
Sign up to set email alerts
|

Full-genome analysis of resistance gene homologues in rice

Abstract: The availability of the rice genome sequence enabled the global characterization of nucleotide-binding site (NBS)-leucine-rich repeat (LRR) genes, the largest class of plant disease resistance genes. The rice genome carries approximately 500 NBS-LRR genes that are very similar to the non-Toll/interleukin-1 receptor homology region (TIR) class (class 2) genes of Arabidopsis but none that are homologous to the TIR class genes. Over 100 of these genes were predicted to be pseudogenes in the rice cultivar Nipponba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
184
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(196 citation statements)
references
References 68 publications
5
184
1
3
Order By: Relevance
“…Paralog 1 was predicted to code for a 905-aa protein typical of cereal (non-TIR class; ref. 30), NBS-LRR proteins (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paralog 1 was predicted to code for a 905-aa protein typical of cereal (non-TIR class; ref. 30), NBS-LRR proteins (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…If other R genes function in heterologous cereal backgrounds, it will have a significant impact on strategies to improve disease resistance in our most important crops. Considering that the NBS-LRR genes account for Ϸ1% of genes in the rice genome (30,42) and the thousands of different species of grasses, this could provide a deep resource of R genes to control different phytopathogens. In the case of Rxo1, the maize gene confers broad resistance to a diverse group of X. o. pv.…”
Section: Discussionmentioning
confidence: 99%
“…The correspondence between major R genes and QRL in genomic locations has been reported in several studies involving rice blast (11)(12)(13). Because of the low resolution in QTL mapping, this association between CR genes and QRL for PR could result from differentiated functions of different members in the R gene families (14), from the secondary functions of the same alleles of the R genes that can activate pathways leading to PR, or from both. This uncertainty will be resolved when all rice R genes are cloned in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The RGA marker (NBS-1) mapped in the proximity of QTL2. Given the abundance of RGA sequences in plant genomes, many of which are not functional (Leister, 2004;Monosi et al, 2004), the colocation of this RGA marker with QTL2 is not sufficient to conclude that the identified RGA is involved in crown rust resistance. A more detailed study of the identified RGA sequence is necessary before it can be determined whether it is part of a functional gene and whether this gene is involved in crown rust resistance.…”
Section: Qtl Analysismentioning
confidence: 99%